Analysis of the arm swing technique during the spike attack in elite beach volleyball. (4th May 2019) - Giatsis, George; Schrapf, Norbert; Koraimann, Tobias; Tilp, Marcus
ABSTRACT: The spike is the most frequent type of attack in elite beach volleyball. The aim of this study was to investigate the arm swing techniques during the spike of world elite beach volleyball players. Ninety-six male players were analysed using video recordings from the 2017 Beach Volleyball World Championship. The arm swing movement techniques (bow-and-arrow high and low, snap, and circular) of each player were classified by two experts. Intra-rater and inter-rater reliability were analysed using Cohen's Kappa statistic. Absolute and relative frequencies of the techniques were recorded and their relation to performance parameters was calculated with χ 2 test or multinomial distribution. Intra-rater reliability of both experts (κ = .965, p < .001 and κ = .947, p < .001, respectively) and inter-rater reliability (κ = .930, p < .001) were very high. Analyses revealed that the two predominant techniques were bow-and-arrow low (51.6%) and bow-and-arrow high (37.4%). However, 11% of the players utilise other techniques (circular: 6.6%; snap: 4.4%). There were no differences ( p > .05) in performance between players predominately utilising the various arm swing techniques. Although the observed techniques seem to not affect performance, future studies should investigate their effect on injuries in beach volleyball.